Is Customary Marine Tenure in Ambon Lease Exist? A Preliminary Study on Integrated Designing Integrated Management Schemes between Customary and Local Governance System to Support in Coastal Community Empowerment - Hernandi, Andri; Mei Ling, Marisa; Abdulharis, Rizqi (Indonesian Journal of Geospatial, 2012)
Abstract. The customary communities in Indonesia have employed a range of resource management techniques to limit marine resource use. Localized control over marine resources, commonly known as Customary Marine Tenure (CMT), is the legal and cultural foundation for many of these practices. This paper outlines the general characteristics of CMT in Maluku Islands in which these characteristics overlap with modern right-based coastal management. It also examines the effectiveness of CMT regimes at regulating marine resource use and access by focusing on a particular case from the Ambon Lease. The custom institutional robustness and vulnerability of CMT is assessed by examining various performance criteria for three communities in the Ambon Lease that is Ambon, Haruku, and Saparua Island. These criteria could be identified by coverage of the area, social right holding unit and legality, and its enforcement. The results show that a number of historical processes have shaped CMT systems into heterogeneous and dynamic institutions, and that CMT regimes can vary even on small geographical scales. Understanding the circumstances in which CMT regimes are more likely to be successful has facilitated the design and implementation of integrated management fishery between customary and local government institution for protecting particular species and habitats in the region. More generally, the paper proposes that by discerning the effectiveness of local governance institutions at regulating resource use and access taking into consideration that these are embedded in particular customary system contexts. This knowledge can also assist in designing integrated management schemes between customary and local governance system. This integration is particularly relevant when these policies are to be implemented in coastal communities that have or have had traditional rights-based coastal management systems of their own that more socio-culturally homogeneous. Given the long history of coastal management, it is now of vital importance to design innovative coastal management prescriptions that integrate engineering and social science research more comprehensively. Keywords: Customary Marine Tenure, Integrated Coastal Management